Verbal and Non-Verbal Speech in the Emotions of Sadness in the FilmAir Mata di Ujung Sajadah: A Psycholinguistic Analysis - Maretha Nindy Nuraini; Eti Setiawati (Jurnal Sastra Indonesia, 2025)
Psycholinguistic research that examines the emotion of sadness in films is still limited, especially those that focus on the combination of verbal and non-verbal utterances, so this study aims to fill this gap by analyzing how verbal and non-verbal utterances and the impact of the emotion of sadness in films. This study uses a descriptive qualitative approach to understand holistically how verbal and non-verbal utterances in the film Air Mata di Ujung Sajadah describe the emotion of sadness and does not include measurement and description in the form of words. The data collection technique used is the listening and recording technique. Listening and recording are done by observing and recording verbal and non-verbal utterances in the emotion of sadness in the film Air Mata di Ujung Sajadah, writing dialogues with their duration, and classifying the form of verbal and non-verbal utterances and the impacts that occur. The study's results prove that there are 19 emotions of sadness, and three impacts occur in the emotion of sadness in the film Air Mata di Ujung Sajadah. This study contributes to increasing insight in psycholinguistics, especially in the emotion of sadness in films.